Childhood awaits every person - Walton, Chris (International journal of children's spirituality, 2015)
This article briefly describes the activity we call Magic Spots (others use the name Sit-spots), silent solitude in the natural world with children; explores the notion of metaxic space, the space between one and another, and with the help of children's voices introduces the important of the context in which of facilitating times of solitude in the natural world (which I call stretching this in-between space enough for children to experience spirit') takes place. The second half of the article shares examples of children's own agency of their spirituality and finally, reflects on the characteristics needed for adults who are privileged to accompany them.